Acute depletion of complement C3 with cobra venom factor attenuates memory deficits induced by status epilepticus - Nicole D. Schartz; Yibo Li; Alexandra L. Sommer; Amy L. Brewster (Epilepsia Open)
Abstract Objective Status epilepticus (SE) significantly increases the risk for the development of unprovoked seizures, memory loss, and temporal lobe epilepsy. Our prior studies showed that SE increases complement C3 signaling in the hippocampus, which parallels memory deficits. Additionally, C3 knockout (KO) mice were protected against SE‐induced memory impairments, suggesting a mechanistic role for C3 in this pathophysiology. In this study, we utilized cobra venom factor (CVF), a structural analog of C3 that results in its depletion, to investigate the protective effects of post‐SE C3 ablation on memory deficits that develop during epileptogenesis. Methods SE was induced in male rats using the chemoconvulsant pilocarpine. Two weeks later, control (C) and SE rats were treated with either vehicle (V) or CVF. Recognition memory was assessed using the novel object recognition (NOR) test in four groups (C + V, C + CVF, SE + V, and SE + CVF). Immunoblotting was used to measure hippocampal protein levels of C3 along with synaptic, astrocyte, and blood–brain barrier (BBB) stability markers, Psd95, GFAP, and albumin, respectively. Results In the NOR test, rats in the C + V and C + CVF groups spent more time exploring the novel object. SE + V rats explored both objects equally, while SE + CVF rats spent significantly more on the novel object, suggesting a rescue of cognitive performance by CVF. While CVF‐mediated C3 depletion did not restore normal protein levels of Psd95 or GFAP in hippocampi of SE + CVF rats, CVF treatment attenuated SE‐induced extravasation of albumin, suggesting potential rescue of BBB stability. Significance Our findings indicate that acute C3 depletion with CVF can attenuate memory deficits that develop during SE‐induced epileptogenesis. This finding further suggests that targeting C3 could hold promise in addressing cognitive comorbidities associated with SE and acquired epilepsy. Plain Language Summary A long‐lasting seizure, known as status epilepticus (SE), can raise the chance of having more seizures in the future and can lead to memory problems. While the exact reasons for these issues are not completely known, it is believed that brain inflammation might be involved. In this study, we show that the activation of the body's immune response, especially a part called the C3 component, plays a role in the memory problems that occur after an episode of SE.